Association HIV/AIDS Knowledge with Stigma toward People Living with HIV/AIDS among Adolescents - Frisca Yunadi; Bambang Budi Raharjo; Susanti Susanti; Gita Arisara; Tri Fitri Yana Utami; Septiana Indratmoko (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
HIV/AIDS remains a major public health challenge worldwide, particularly among adolescents. Limited knowledge and misconceptions about HIV transmission often contribute to stigmatizing attitudes toward people living with HIV/AIDS (PLWHA), creating social and psychological barriers that may reduce access to prevention, testing, and treatment services. This study aimed to examine the relationship between adolescents' level of knowledge regarding HIV/AIDS and their stigma toward people living with HIV/AIDS. A quantitative correlational study with a cross-sectional design was conducted among all active members of Posyandu Remaja Rahayu. Using a total sampling technique, 36 adolescents were recruited as respondents. Data were collected through a structured questionnaire assessing HIV/AIDS knowledge and stigma toward PLWHA. The study showed the majority respondents 58.3% demonstrated good knowledge of HIV/AIDS, while 41.7% had poor knowledge. Regarding stigma, 69.4% exhibited low stigma and 30.6% demonstrated high stigma toward people living with HIV/AIDS. Statistical analysis found a significant association between HIV/AIDS knowledge and stigma (χ² test, p = 0.001), indicating that adolescents with better knowledge tended to have lower levels of stigma. HIV/AIDS knowledge was significantly associated with stigma toward people living with HIV/AIDS among adolescents. Strengthening comprehensive HIV/AIDS education through youth health posts and school-based health promotion programs may improve adolescents' understanding and contribute to reducing stigma toward people living with HIV/AIDS.